(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to measure and analyze the impact of fiscal policy on real gross domestic product in Libya during the period 1995-2024, using the Autoregressive Distributed Lag (ARDL) model, which is characterized by its ability to handle mixed-integrated time series. The study relied on annual data (30 observations) covering a sufficient and large time period for applying the ARDL model and achieving reliable results. Real GDP was used as the dependent variable, while public expenditure, oil revenues, exchange rate, and inflation rate were used as independent variables. The results of the Bounds Test showed a long-run cointegration relationship among the variables at the 1% significance level. The results also showed that the long-run elasticity coefficient of public expenditure was (0.4235), meaning that a 1% increase in government spending leads to a 0.42% increase in real GDP in the long run. Oil revenues were found to have a significant and positive impact on GDP, while the exchange rate and inflation rate had a negative and significant impact. The study recommended diversifying the production and revenue base, rationalizing public expenditure, adopting a flexible exchange rate policy, and utilizing the results of the ARDL model in financial planning and forecasting.